A phylogeny of the tinamous (Aves: Palaeognathiformes) based on integumentary characters - Bertelli, Sara Beatriz (2002)
A cladistic analysis of the tinamous, including the 47 currently recognized species and some distinct subspecies, was conducted based on 80 integumentary characters from adult and natal plumage, ramphoteca (corneum sheath of bill), and podoteca (horny scales of legs). For the adult plumage (50 characters), we studied feather pigmentation patterns from different pterylae (feather tracts). A criterion of overlap of basic pigmentation elements was used to assign costs to the transformation between the states in most of these characters in such a way that transformations between more similar conditions were less costly. The consensus tree was almost fully resolved, and about 50% of its groups were relatively well supported. Because the only outgroup that could be used provided a poor root, two possible rootings of the ingroup subtree were considered; in both cases, only one of the two traditional subfamilies (the steppe tinamous) was recovered, and the other (the forest tinamous) appeared as paraphyletic. The results of the present analysis are compared with those from an osteological data set, using a strict supertree technique. The combined tree has a large number of nodes, indicating a high degree of congruence between the two data sets.